2023
DOI: 10.3390/clockssleep5020021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Biological Clock and Inflammatory Bowel Disease

Jonathan Giebfried,
Axel Lorentz

Abstract: The biological clock is a molecular oscillator that generates a 24-hour rhythm in accordance with the earth’s rotation. Physiological functions and pathophysiological processes such as inflammatory bowel diseases (IBD) are closely linked to the molecular clock. This review summarizes 14 studies in humans and mice on the interactions between the biological clock and IBD. It provides evidence that IBD negatively affect core clock gene expression, metabolism and immune functions. On the other hand, disruption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…TRIM40 drives IBD pathogenesis by targeting cell-cell junctions in the mucosal epithelial barrier and promoting inflammation in the gut ( Noguchi et al 2011 , Kang et al 2023 ). Disturbances in the circadian rhythm are also linked to IBD manifestations ( Giebfried and Lorentz 2023 ); for instance, CLOCK expression is disrupted in IBD patients ( Weintraub et al 2020 , Giebfried and Lorentz 2023 ). Interestingly, BoostDiff identifies an edge between CLOCK and STAT3 , which could point to a candidate regulatory mechanism where the circadian clock influences STAT3 , a known driver of the CD phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…TRIM40 drives IBD pathogenesis by targeting cell-cell junctions in the mucosal epithelial barrier and promoting inflammation in the gut ( Noguchi et al 2011 , Kang et al 2023 ). Disturbances in the circadian rhythm are also linked to IBD manifestations ( Giebfried and Lorentz 2023 ); for instance, CLOCK expression is disrupted in IBD patients ( Weintraub et al 2020 , Giebfried and Lorentz 2023 ). Interestingly, BoostDiff identifies an edge between CLOCK and STAT3 , which could point to a candidate regulatory mechanism where the circadian clock influences STAT3 , a known driver of the CD phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…In ulcerative colitis, 50 genes were expressed differentially, and 27 were upregulated. It was observed that the clock genes Arntl2 and RorA were upregulated, while Csnk2B , Npas2 , Per1 , and Per3 were downregulated [ 38 , 39 ]. This could be related to the manifestation of these pathologies in subjects exposed to conditions of desynchronization such as shift work or jet lag [ 40 , 41 ].…”
Section: Circadian Rhythms In the Enteral Systemmentioning
confidence: 99%
“…Cholesterol levels are said to be lowest between 2 and 6 p. m. and highest at 6 am. [51,52]. For hypercholesterolemia, chronotherapy can be performed by scheduling the medicine following the circadian cycle.…”
Section: Diseasementioning
confidence: 99%